2022
DOI: 10.3390/foods11223607
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant Activity of Areca Nut Polyphenol Extracts on RAW264.7 Cells

Abstract: Chewing areca nuts is a popular hobby in the Asian region, and areca nuts are rich in polyphenols, although some alkaloids are included. In this study, we explored the antioxidant activity of areca nut polyphenols (ANP) in lipopolysaccharides (LPS)-stimulated RAW264.7 cells. The results revealed that ANP reduced the level of reactive oxygen species (ROS) in LPS-stimulated RAW264.7 cells and enhanced the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1). RNA-seq analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…It is mostly used to stimulate cells to produce inflammation. ANP has antioxidant and anti-inflammatory effects; it has been demonstrated in previous studies that ANP attenuates cellular oxidative stress and inflammation induced by LPS through the Nrf2/HO1 and MAPK pathways [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is mostly used to stimulate cells to produce inflammation. ANP has antioxidant and anti-inflammatory effects; it has been demonstrated in previous studies that ANP attenuates cellular oxidative stress and inflammation induced by LPS through the Nrf2/HO1 and MAPK pathways [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…ARE has been also reported to cause the accumulation of reactive oxygen species (ROS) which further cause cholesterol accumulation in the liver, leading to NAFLD [ 37 , 38 ]. Previous study revealed that ANE containing both polyphenols and ARE had a ROS scavenging ability and antioxidant ability [ 39 , 40 ], and ANP containing only polyphenols significantly scavenged LPS-induced ROS [ 41 ]. To provide a reliable understanding of the function and safety of the areca nut, we assessed the effects of whole areca nut extract, polyphenol extract, and ARE on a WD-induced NAFLD mouse model by investigating the changes in metabolic characters and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the areca nut is the fourth most commonly used psychoactive substance after tobacco, alcohol and caffeine [3,4]. Areca nuts can help with resistance to bacteria, removal of parasites and facilitation of digestion [5]. Estimated 600 million people consume areca nuts, predominantly in the southern parts of Asia such as China (Hainan and Taiwan), Vietnam, Indonesia, Myanmar and the Pacific regions [6].…”
Section: Introductionmentioning
confidence: 99%